1982
DOI: 10.1007/bf02006139
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of 0-group eel larvae (Anguilla sp.) in the Sargasso Sea

Abstract: Both Atlantic eel species (Anguilla anguilla and A. rostrata) were collected in the Sargasso Sea during the 1979 cruise of the F. R. V. "Anton Dohrn" and R. V. "Friedrich Heincke". A total of 3,097 0-group larvae were caught during 80 hauls using the Isaacs Kidd Midwater Trawl (55 hauls) and the 9-fold opening and closing net MOCNESS (25 hauls). 11 hauls of the MOCNESS indicated that the larvae showed a preference for the 150-175 m water depth during daytime and for the 50-75 m depth during night. The northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 13 publications
6
72
0
Order By: Relevance
“…This would imply that eggs of the same species are spawned in different water layers or sink to different depths with highly different temperatures. As, in the present material, very small specimens of both species came from the same hauls (Schoth & Tesch, 1982) this seems improbable. According to Blaxter (1969) there usually is a V-relation in changes of vertebrae with different temperatures, i.e.…”
Section: -mentioning
confidence: 53%
See 1 more Smart Citation
“…This would imply that eggs of the same species are spawned in different water layers or sink to different depths with highly different temperatures. As, in the present material, very small specimens of both species came from the same hauls (Schoth & Tesch, 1982) this seems improbable. According to Blaxter (1969) there usually is a V-relation in changes of vertebrae with different temperatures, i.e.…”
Section: -mentioning
confidence: 53%
“…Five specimens, longer than 30.0 mm (2 x 31.0 ram; 2 x 31.5 ram; 1 × 32.0 ram), have not been considered in the analysis; later on they turned out to be A. rostrata. For information on the station net in the Sargasso Sea, the geographical distribution of the larvae and the methods of fishing, see Schoth & Tesch (1982).…”
Section: Methodsmentioning
confidence: 99%
“…It was originally attempted in the present study to assess this small zooplankton fraction in the Sargasso Sea as potential food supply for eel larvae. The spawning area of the American and European eel (Anguilla rostrata and A. anguilla) is located in the southern part of the Sargasso Sea, and recent studies by Schoth & Tesch (1982) have demonstrated that the youngest larvae occur mainly in this area. However, not one single food organism has yet been found in the guts of the eel larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The spawni.ng locations in the Sargasso Sea and the general distributions of the leptocephali of the American and European eels are relatively well known (Schmldt 1922, Schoth & Tesch 1982, Kleckner et al 1983, Boetius & Harding 1985, Tesch & Wegner 1990) in comparison to the other 12 families o' f anguilliform eels whose leptocephali are commonly found in the WNA. Some information is available on the distributions and diets of adult eels in the WNA (Bohlke & Chaplin 1968, Bohlke 1989), but little is known about the reproductive ecology of most marine eels, other than a few observations of apparent spawning migrations (Cohen & Dean 1970), reproductive behavior (Moyer & Zaiser 1982, Ferraris 1985, the presence of eggs and leptocephali (Castle & Robertson 1974) and gonadal morphology (Bohlke 1989, Fishelson 1992) In a few shelf species.…”
Section: Introductionmentioning
confidence: 99%